2010
DOI: 10.1093/nar/gkq268
|View full text |Cite
|
Sign up to set email alerts
|

An extended set of PRDM1/BLIMP1 target genes links binding motif type to dynamic repression

Abstract: The transcriptional repressor B lymphocyte-induced maturation protein-1 (BLIMP1) regulates gene expression and cell fate. The DNA motif bound by BLIMP1 in vitro overlaps with that of interferon regulatory factors (IRFs), which respond to inflammatory/immune signals. At such sites, BLIMP1 and IRFs can antagonistically regulate promoter activity. In vitro motif selection predicts that only a subset of BLIMP1 or IRF sites is subject to antagonistic regulation, but the extent to which antagonism occurs is unknown,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
57
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 54 publications
(64 citation statements)
references
References 73 publications
7
57
0
Order By: Relevance
“…As expected, the predicted Blimp-1-binding motif, (N)(N)(T/A)GAAAGT, is similar to the previously identified sites from two independent studies, (A/C)AG(T/C)GAAAG(T/C)(G/T) 25 and GTGAAAGTand G(N) GAAAGT. 26 In addition, we found that, in MM cells, a large proportion of the genes that Aiolos bound directly had the consensus binding sequence TGAAACT (site 2), which is similar to the Blimp-1 consensus site. Another consensus binding sequence, A(N)AGGAA (site 1), was also found and is similar to that reported for Aiolos, ACAGGAAGT, in T cells.…”
Section: Discussionmentioning
confidence: 71%
“…As expected, the predicted Blimp-1-binding motif, (N)(N)(T/A)GAAAGT, is similar to the previously identified sites from two independent studies, (A/C)AG(T/C)GAAAG(T/C)(G/T) 25 and GTGAAAGTand G(N) GAAAGT. 26 In addition, we found that, in MM cells, a large proportion of the genes that Aiolos bound directly had the consensus binding sequence TGAAACT (site 2), which is similar to the Blimp-1 consensus site. Another consensus binding sequence, A(N)AGGAA (site 1), was also found and is similar to that reported for Aiolos, ACAGGAAGT, in T cells.…”
Section: Discussionmentioning
confidence: 71%
“…Thus, it will be important to understand the likely oncogenic mechanisms controlling these transcriptional events. Significantly, BLIMP1 has been shown to bind the FOXP1 locus, 40 and thus BLIMP1 mutation 18 may drive ABC-DLBCL lymphomagenesis at least in part by mis-regulating FOXP1 isoform expression.…”
Section: Discussionmentioning
confidence: 99%
“…This sequence can also be recognized by interferon regulatory factors (IFRs, see Glossary, Box 1), and Prdm1 and IRFs can antagonistically regulate promoter activity (Kuo and Calame, 2004). More recently, DNA binding of Prdm1 was shown to be abrogated by CpG methylation, adding complexity to transcriptional regulation by this protein, and suggesting a model in which Prdm1 could be actively excluded from a subset of its target sites, once silencing at the level of DNA methylation has been established (Doody et al, 2011).…”
Section: Box 2 Prdms In Cancer and Other Diseasesmentioning
confidence: 99%